A comprehensive study on abnormalities associated with red blood cells in Saudi adult patients - Alsagaby, Suliman A. (International Journal of Health Sciences, 2021)
Objectives: The present work aimed to study red blood cells (RBCs) parameters data of Saudi patients to cover hematological patterns and evaluate abnormality prevalence. Methods: RBCs parameters data of adult Saudi patients who attended Prince Nasser bin Saad Al-Sudairy Hospital in Alghat province between January 1, 2019 and December 31 2019 were collected and studied. Results: The study included 1663 patients; 814 (49%) males and 849 (51%) females. The proportion of patients with anemia as defined by low levels of hemoglobin (Hb) was similar in males (20%) and females (21%) with a clear drop in the percentage of anemia among females aged 51–65 years. Data from Alghat province showed bigger proportion of patients with macrocytic anemia (high mean cell volume [MCV] = 35% in males and 25% in females) compared with microcytic anemia (low MCV = 7% in males and 19% in females). Microcytic hypochromic anemia was found to be common in women (18%) compared with men (6%), with the highest prevalence being detected in females (31%) at age 46–50. Conclusion: This is the first study to shed light on RBCs data from Alghat province, and provide insights into anemia in adults. Anemia was seen in 20–21% of the patients, with macrocytic anemia being the most prevalent type of anemia in the studied population.